Seroprevalence of Hepatitis C and factors associated with this in crack users - Laís Carvalho de Sá; Telma Maria Evangelista de Araújo; Rosane Harter Griep; Viriato Campelo; Claudete Ferreira de Souza Monteiro (Universidade de São Paulo, 2013)
OBJECTIVE: to investigate the seroprevalence of hepatitis C in crack users in Piauí. METHOD: seroepidemiological survey, undertaken in the Psycho-Social Care Centers for Drugs and Alcohol (CAPS AD) in Piauí in the period December 2011 to May 2012. A questionnaire was administered and blood samples were collected for serological research. Fisher's exact test and the Mann-Whitney test were used, with a level of significance of (p<0.05). RESULTS: the prevalence of Anti-HCV was 05 (1.4%) and 04 (1.1%) for the RNA-HCV. There was a statistically significant association between hepatitis C (serological marker RNA-HCV) and age, being resident at home, length of use of crack, interruption of the use of crack, and the habit of sharing the crack pipes. CONCLUSION: the findings support the need to implement health policies aimed at crack users, due to the accelerated process of physical and psychological deterioration to which these are subject.